Synthesis and biological evaluation of phosphate isosters of fosmidomycin and analogs as inhibitors of Escherichia coli and Mycobacterium smegmatis 1-deoxyxylulose 5-phosphate reductoisomerases. Issue 2 (15th January 2017) - Munier, Mathilde; Tritsch, Denis; Krebs, Fanny; Esque, Jérémy; Hemmerlin, Andréa; Rohmer, Michel; Stote, Roland H.; Grosdemange-Billiard, Catherine
Graphical abstract: Inhibitory activity against E. coli and M. smegmatis DXRs. Abstract: Hydroxamate analogs of fosfoxacin, the phosphate homolog of fosmidomycin, have been synthesized and their activity tested on Escherichia coli and Mycobacterium smegmatis DXRs. Except for compound4b, the IC50 values of phosphate derivatives are approximately 10-fold higher than those of the corresponding phosphonates. Although their inhibitory activity on Escherichia coli DXR is less efficient than their phosphonate analogs, we report the ability of phosphate compounds to inhibit the growth of Escherichia coli. This work points out that the uptake of fosfoxacin and its analogs is taking place via the GlpT and UhpT transporters. As expected, these compounds are inefficient to inhibit the growth of M. smegmatis growth inhibition probably due to a lack of uptake.